2013
DOI: 10.3941/jrcr.v7i1.1276
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral rupture from aberrant Foley catheter placement: A case report

Abstract: We present the case of a 59 year old female with history of severe neurologic dysfunction from advanced multiple sclerosis who presented with lethargy and oliguria several hours after urethral Foley catheterization. A contrast-enhanced CT scan of the abdomen/pelvis showed an aberrantly placed Foley catheter with its balloon inflated in the proximal left ureter, a rare complication of Foley catheterization with only 5 other cases reported. Incomplete ureteral rupture was demonstrated and confirmed by a followup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 12 publications
0
22
0
7
Order By: Relevance
“…Frickmann et al [4] reported one case of ureteral rupture during a suprapubic vesical catheter change in a patient with prostate adenoma. The other two cases of ureteral rupture after urethral Foley catheterization were reported in female patients [56]. The case reported here is the first case of ureteral rupture induced by an indwelling suprapubic catheter in a male patient with neurogenic bladder caused by SCI.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Frickmann et al [4] reported one case of ureteral rupture during a suprapubic vesical catheter change in a patient with prostate adenoma. The other two cases of ureteral rupture after urethral Foley catheterization were reported in female patients [56]. The case reported here is the first case of ureteral rupture induced by an indwelling suprapubic catheter in a male patient with neurogenic bladder caused by SCI.…”
Section: Discussionmentioning
confidence: 78%
“…Catheter localization in the ureter is a rare complication; in fact, only 17 cases of an indwelling urethral or suprapubic catheter located in the ureter have been reported to date, among which three cases showed ureteral rupture after catheterization [456]. …”
Section: Introductionmentioning
confidence: 99%
“…1 Gentle insertion of the catheter should always be undertaken because forceful and rough manipulation during catheterization induces urethral injury. 2 Life-threatening adverse effects induced by Foley catheter insertion, such as urethral rupture, are not frequent, 3 and previous studies have shown that placement can be safely achieved even by medical staff members other than urology experts. 4,5 Placement of a Foley catheter was necessary to resolve the urinary retention in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Les lésions iatrogènes sont secondaires à des interventions urologiques (42 %), gynécologiques (34 %) ou de chirurgie générale (24 %). L'uretère distal est majoritairement en cause (91 %) [1].…”
Section: Discussionunclassified